Capital Structure, Audit Committee, Company Growth and Company Value - Haditya, Avisena Nurul (EAJ (Economic and Accounting Journal), 2022)
Company value is one of the things that underlies investors making investment decisions. Investors are more interested in investing their shares in companies with good performance in increasing their value. It is intended that investors can predict optimal profits to be obtained in the future. This study examines the effect of capital structure, audit committee, and company growth on Company value. The research population was 54 industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period with a purposive sampling technique, namely selecting samples based on specific criteria as desired by the researcher so that the number of samples obtained was 26 companies from observations for 5 ( five years. The data used in this study is secondary data in the form of financial reports and annual reports. The study shows that capital structure and company growth have a positive effect on company value, while the audit committee does not affect company value.